The Bethesda handbook of clinical hematology - Rodgers, Griffin P.; Young, Neal S. (Wolters Kluwer, 2019)
Bridging the gap between science and clinical practice, The Bethesda Handbook of Clinical Hematology, Fourth Edition , provides concise, up-to-date coverage of 'need to know' information on the diagnosis and treatment of blood and bone marrow disorders. Written by nationally recognized experts and senior fellows at the National Institutes of Health, and at leading research institutions throughout the United States, this essential pocket reference is logically organized by disease category and features a reader-friendly format that includes tables, algorithms, illustrations, and bulleted lists that highlight key information. Discusses the pathophysiology, natural history, risk factors, diagnosis, management, and follow-up of common hematological diseases. Contains new information on diagnosis, treatment and management of myelodysplastic and myeloproliferative disorders; leukemias and lymphomas; disorders of hemostasis and thrombosis. Features new diagnostic and treatment strategies, updated references, and revised information throughout. Ideal for the student, resident, or fellow on a hematology or oncology service, as well as the internist, hospitalist, family practitioner, and pediatrician who sees patients with blood diseases. Perfect as an everyday reference or for board review.